1993
DOI: 10.1002/1097-0142(19931215)72:12<3694::aid-cncr2820721222>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemotherapy, a new antitumor treatment. First clinical phase I-II trial

Abstract: Background. Electrochemotherapy is a new antitumor treatment consisting of electrical pulses administered to the tumor several minutes after intravenous injection of bleomycin. In mice, important antitumor effects were observed on subcutaneously transplanted tumors and on spontaneously occurring mammary carcinomas. Cures were obtained after one single treatment combining bleomycin and electric pulses. In humans, permeation nodules seemed an adequate oncologic situation to assay this new procedure. The authors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
233
0
5

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 407 publications
(244 citation statements)
references
References 11 publications
2
233
0
5
Order By: Relevance
“…[2][3][4][5] Clinical trials of electric field-mediated drug delivery have been conducted to treat tumors. 6,7 These studies demonstrate that it is feasible and safe to use electric fields to facilitate drug and gene delivery.…”
Section: Introductionmentioning
confidence: 90%
“…[2][3][4][5] Clinical trials of electric field-mediated drug delivery have been conducted to treat tumors. 6,7 These studies demonstrate that it is feasible and safe to use electric fields to facilitate drug and gene delivery.…”
Section: Introductionmentioning
confidence: 90%
“…22 Moreover, because of the antitumour efficacy of this approach, clinical trials were rapidly performed. 23,24 This approach was termed electrochemotherapy, and the pulse conditions, used in almost all the published clinical trials, [25][26][27] were eight identical square wave pulses of 100 ms and 1300 V/cm at a repetition frequency of 1 Hz using external electrodes (transcutaneous pulses). These trials demonstrated that it is possible to deliver in vivo electric pulses to animals and patients and they greatly facilitated the development of the in vivo DNA electrotransfer.…”
Section: In Vivo Delivery Of Electric Pulsesmentioning
confidence: 99%
“…2 The latter has resulted in a new tool to battle cancer, electrochemotherapy, which is based on the application of pulses that induce the electroformation of reversible pores in the cell membrane, thereby allowing the delivery of non-permeant drugs inside tumor cells. 2,3 Membrane pores can also be chemically induced by the use of particular membrane-fluidizing compounds such us dimethyl sulfoxide (DMSO, (CH 3 ) 2 SO), a small amphiphilic molecule that has been shown to enhance cell permeability through the formation of water pores. 4,5 Recently, molecular dynamics (MD) simulations have been used to elucidate the molecular mechanisms leading to pore formation in simple lipid bilayers by both the application of an external electric field [6][7][8][9][10] and the effects of DMSO.…”
Section: Introductionmentioning
confidence: 99%